Building.org : a manager's guide to creating successful websites for international organisations - Nuk, Igor (DiploProjects MsidaMT, 2002)
Provides a guide on how to establish a website. Covers the fundamentals viz. deciding whether to outsource a web project or do it in-house; defining goals, priorities and the key factors for success. Deals with getting the right skills on board, choosing the right technology solution, creating good content, managing the web project and evaluating user response.